Hydrogen production via photoreforming of wastewater under LED light–driven over CuO@exfoliated g–C3N4 nanoheterojunction - Thurga Devi, Munusamy; Chin, Sim Yee; Khan, Md. Maksudur Rahman (Elsevier, 2022)
As the global interest heading towards net zero emission by 2050, clean hydrogen production technologies becomes limelight among the research community. Besides, the generation of large quantity of industrial wastewaters creates huge dilemma and needs special attention. In this work, synthetic wastewater using formaldehyde (FA) as a model organic pollutant was utilized to produce hydrogen. The photocatalyst, CuO@exfoliated g–C3N4 nanoheterojunction was synthesized by an acid treatment and facile chemical precipitation technique. XRD results confirmed the successful formation of exfoliated g–C3N4 by expanding the interlayer spacing of the nanosheets via shifting of characteristic peak of graphite towards lower 2θ from 27.97° to 27.04°. Meanwhile, the BET surface area of CuO@exfoliated g–C3N4 (199.3 m2/g) was remarkably enhanced as compared to bulk g–C3N4 (34.5 m2/g) and exfoliated g–C3N4 (104.4 m2/g). The existence of large pores (3.55 cm3/g) in CuO@exfoliated g–C3N4 promotes the accessibility of reactant to the surface active sites, escalating the redox reactions. Study on hydrogen production via photoreforming of aqueous formaldehyde over the prepared photocatalysts were conducted. Interestingly, hydrogen generated using CuO@exfoliated g–C3N4 (3867 μmol/g) was greatly enhanced by 7 times and 13 times than the counterparts catalysts, exfoliated g–C3N4 (532 μmol/g) and pure CuO (271 μmol/g) respectively. By employing the CuO@exfoliated g–C3N4 nanoheterojunction, the optimum hydrogen with apparent quantum efficiency (AQE) of 5664 μmol/g and 22% were obtained respectively. Besides, S–scheme reaction mechanism was proposed based on heterojunction formed between the p–type CuO and n–type exfoliated g–C3N4 nanosheets.